Depression and cognitive impairment in Malaysian elderly: insights from a nationwide study - Nikmat, Azlina Wati; Raduan, Nor Jannah Nasution; Hashim, Nurul Azreen; Ahmad Tarmizi, Noor Azleen; Affandi, Nor Anita; Hairoman, Nor Farahdila; Hafiz Ismail, Muhd Zulfadli; Tengku Kamarulbahri, Tengku Mohd Saifuddin (International Journal of Public Health Science (IJPHS), 2025)
Depression and cognitive impairment are two prevalent mental health conditions among older adults. This study aimed to investigate the factors associated with cognitive impairment among older adults with depression in Malaysia. Data were drawn from the National Health and Morbidity Survey 2018, a nationwide, cross-sectional study using a two-stage stratified cluster sampling. The sample included respondents aged 50 years and above. Cognitive impairment was assessed using the identification and intervention for dementia in the elderly (IDEA) screening tool, while depression was identified using the validated Malay version of the Geriatric Depression Scale (M-GDS-14). Key variables examined included sociodemographic characteristics, physical activity levels, and social support. Bivariate and multiple logistic regression analyses were performed to identify factors significantly associated with cognitive impairment. Results indicated that cognitive impairment was significantly higher among physically inactive individuals (AOR = 2.70, 95% CI: 0.21, 0.65) and those with low to fair social support (AOR = 1.79, 95% CI: 1.12, 2.86). These findings highlight the importance of incorporating physical and social activities into care plans for elderly patients with depression, particularly those with cognitive impairments.